The Sosialisasi Pola Pembudayaan Pengamalan Sila Pertama Ketuhanan Yang Maha Esa Dalam Kehidupan Sehari-hari bagi Mahasiswa Program Studi Manajemen di Lombok, NTB - opan, opansatriamandala; Yusika Paramida, Ari; Efendi, Saparudin; Rahmatar, Ana; Nadia Nirwana, Baiq; Dwi Putri Marswandi, Ega (Al-Madani: Jurnal Pengabdian Pada MAsyarakat, 2023)
The rapid development of the current era of globalization is increasingly suppressing the process of cultural acculturation, especially the influence of western culture, which seems to dominate and is always the trend-centre, the habits and lifestyle of western people seem to be a modern mirror in people's lives. This situation continues to erode local culture and wisdom which is the heritage of the Indonesian archipelago. The ability to face challenges that are very basic and will hit national, social and political life, even mental and national life, the final stronghold is national belief based on the State of Pancasila. Pancasila is a bulwark in facing challenges in the current era of globalization which is increasingly developing. Applying Pancasila values to society, Pancasila is an ideology and foundation of the Pancasila state which is the foundation of all decisions made by the Indonesian nation. Which also means that Pancasila also represents the personality of the Indonesian nation itself. The word Pancasila originates from Indian Sanskrit, namely the word panca which means five, while the word sila has a basic meaning. So the term Pancasila according to each meaning of the word is five basic, from which each symbol of Pancasila is created, which is five, and the contents of Pancasila are also 5 according to the meaning of the word Pancasila.